2015
DOI: 10.3928/00904481-20150910-11
|View full text |Cite
|
Sign up to set email alerts
|

Monthly Periods—Are They Necessary?

Abstract: Menstrual suppression--the use of hormones to delay or eliminate menses--is often used in adolescents to manage conditions associated with the menstrual cycle and to accommodate lifestyle preferences. Reducing the frequency of menstrual bleeding does not cause any known physiologic harm and has potential short-term and long-term advantages. Different methods used for menstrual suppression, however, have associated risks and side effects that need to be weighed against the benefits of controlling menses. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Further, participants understood menstruation as indicators of fertility and reassurance of negative pregnancy status. The women in this study viewed COCs as healthy because they allow for a natural menstrual cycle, yet the ‘menstruation’ experienced on COCs is actually withdrawal bleeding, not menses [7, 8]. Thus, women remain unaware that bleeding experienced when taking a placebo is breakthrough bleeding and not an indicator of pregnancy or fertility status.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, participants understood menstruation as indicators of fertility and reassurance of negative pregnancy status. The women in this study viewed COCs as healthy because they allow for a natural menstrual cycle, yet the ‘menstruation’ experienced on COCs is actually withdrawal bleeding, not menses [7, 8]. Thus, women remain unaware that bleeding experienced when taking a placebo is breakthrough bleeding and not an indicator of pregnancy or fertility status.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrated more frequent menstruation may counteract protective effects of high parity and late menarche [46]. Frequent menstruation may increase ovarian, endometrial, and breast cancer risk [7] and menstruation-related symptoms, such as heavy bleeding, dysmenorrhea, pre-menstrual syndrome, and endometriosis, among others [7–9]. Hormonal contraception, particularly combined oral contraceptives (COC), protect against osteoporosis, pelvic inflammatory disease, and certain gynecological cancers [7, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations